3-D FEM Wear Prediction of Brass Sliding against Bearing Steel Using Constant Contact Pressure Approximation Technique - Kunal Kumar Bose (Japanese Society of Tribologists, 2019)
For predicting the sliding wear in Pin-on-Disc (PoD) tribometer contact, a numerical wear simulation technique is presented in this paper. It is based on the Finite element method (FEM) which incorporates the Archard's wear law and the UMESHMOTION subroutine for calculating the wear depth for a 3-D PoD tribometer contact. FEM is utilized in solving the 3-D contact problem. The geometry is updated using the UMESHMOTION subroutine coupled with the Augmented Lagrangian-Eulerian (ALE) remeshing technique of ABAQUS. But, a significant disadvantage of FEM wear prediction is the enormous computational time required for performing 3-D analysis. Hence, to minimize the computational time, an approximation technique is introduced which accounts for the contact pressure evolution at the contact region. It decreased the simulation time and also preserved the accuracy of 3-D wear prediction. Finally, the results obtained from the simulations are compared with the experiments for brass-on-bearing steel PoD contact. An accuracy of 98.81% was obtained for the 10N and 83.10% for the 30N load.